Students’ Perceived Benefits and Challenges on the Integration of Digital Tools into Undergraduate Thesis Writing in Islamic Higher Education - Rochmahwati, Pryla; Prastikawati, Entika Fani; Ma'mun, Nadiah (Journal of English Teaching and Learning Issues, 2025)
This study examines the role of digital tools in fostering undergraduate students' thesis writing process. While digital tools are now widely applied in academia, limited studies have focused on how these tools impact the quality of students' theses and the challenges they encounter. The qualitative case study design involving 7th-semester students from the English Education Department at an Islamic higher education institution in Ponorogo was employed to explore their perceptions of digital tools through questionnaires, observations, and in-depth interviews. The findings indicated that students use various digital tools, including word processors, reference management software, and data analysis programs. The result of thematic analysis revealed that students perceived digital tools to facilitate the quality, effectiveness, organization of thesis work, and motivation. Although some students faced technical difficulties, unfamiliarity with advanced software features, and resource constraints, they believed learning with digital tools positively influenced their academic performance. The study contributes valuable insights for educators and institutions, informing strategies to optimize the use of digital tools in thesis writing.